Nitric oxide release using natural rubber latex as matrix - Herculano, Rondinelli Donizetti [UNESP]; Tzu, Lee Chen; Silva, Cecilia Pereira; Brunello, Carlos Alberto; Queiroz, Álvaro Antônio Alencar de; Kinoshita, Angela; Graeff, Carlos Frederico de Oliveira [UNESP] (ABM, ABC, ABPol, 2011)
Nitric oxide (NO) is a diffusible messenger that has been involved in numerous physiological processes ranging from vasodilatation and antimicrobial properties to wound healing. The beneficial effects can be attributed to the role NO plays in angiogenesis, inflammation and tissue remodeling. In the present work, a polymeric device for the sustained site specific delivery of nitric oxide using a latex rubber matrix from Hevea brasiliensis which encapsulates the spin trap iron(II)- diethyldithiocarbamate complex (FeDETC) was developed. The release profiles of NO from latex rubber matrix were studied and stability studies were carried out. Electron Paramagnetic Resonance (EPR) signal of NO was detected in the membrane exposed to ambient atmosphere at room temperature (25 °C) even after 350 hours. FTIR spectroscopy data indicated that NO-FeDETC retained its structural and spectroscopic properties upon encapsulation in the latex matrix. The NO delivery system developed in this work as a membrane, presented high stability.
Keywords: nitric oxide; latex membrane; biomaterials; drug delivery system